The Relationship between Retirement Wealth and Householders' Lifetime Personal Financial and Investing Behaviors. Issue 3 (30th October 2013) - ECCLES, DAVID W.; WARD, PAUL; GOLDSMITH, ELIZABETH; ARSAL, GULER
ABSTRACT While previous research indicates wide wealth dispersion at retirement within households with similar lifetime incomes, there have been few attempts to identify personal financial behaviors associated with retirement wealth in households matched for lifetime income. Householders with similar demographics and lifetime income but differing markedly in net worth near retirement were surveyed in terms of personal financial behaviors undertaken during their lifetime. Results revealed key differences between householders with low and high retirement wealth in their financial behaviors and how these were acquired.